Chef Evaluation of the Degree of Doneness of Beef Strip Loin Steaks Cooked to Six End-Point Temperatures - L. L. Prill; L. N. Drey; J. L. Vipham; M. D. Chao; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:The objective of this study was to assess foodservice steak preparation practices and chefs’ abilities to identify degrees of doneness of beef strip loin steaks. Study Description:Beef strip loins (n = 24) from 12 animals representing five quality treatments (Prime, Top Choice, Low Choice, Select, and Select Enhanced) were collected. Steaks were cooked to an end-point temperature of very-rare (130°F), rare (140°F), medium-rare (145°F), medium (160°F), well-done (170°F), or very well-done (180°F). Each cooked steak was cut in half, perpendicular to the long axis of the steak, and photographs were taken immediately of the internal face of the lateral side. A digital survey was developed for chefs for the electronic evaluation of the images of the cooked steaks. Chefs (n = 83) were recruited via email from around the U.S. using an established database of chefs from all segments of the industry. The Bottom Line:Chefs did not report they use the current published degree of doneness temperatures. Additionally, chefs commonly rated steaks one degree of doneness above the degree of doneness category commonly associated with the end-point temperature.
Keywords: chef; degree of doneness; temperature